Factors Influencing Consumer Satisfaction in Online Shopping in Klang, Malaysia - Zhiling, Ch’ng; Har Chris, Ong Siew (Semarak International Journal of Future Tourism and Hospitality Management, 2025)
This study explores the Factors Influencing Consumer Satisfaction in Online Shopping in Klang, Malaysia, shedding light on critical elements such as the online shopping experience, product reliability, and security concerns. With a sample of 200 respondents, the data was analyzed using SPSS to identify the key drivers of consumer satisfaction. Key Findings; 1) Online Shopping Experience: A positive online shopping experience significantly contributes to consumer satisfaction. Elements such as website usability, customer service, and ease of navigation play an important role in shaping how satisfied consumers are with their online shopping experience. 2) Product Reliability: The reliability of products (i.e., accurate descriptions, quality, and timely delivery) also emerged as a major determinant of consumer satisfaction. Consumers value consistency in product quality and delivery, and any discrepancies negatively impact their shopping experience. 3) Security Concerns: While security concerns were shown to affect satisfaction, the relationship is more complex. Consumers are particularly concerned with online payment security, but they are also influenced by the overall trustworthiness of the website, including aspects like data protection and privacy policies. Businesses in Klang looking to improve their e-commerce offerings, the findings suggest that prioritizing a seamless and positive shopping experience, ensuring the reliability of products, and addressing security concerns can significantly enhance consumer satisfaction. By focusing on these areas, companies can foster greater consumer trust and loyalty, which will contribute to sustained growth in the e-commerce sector. This research offers actionable insights for businesses aiming to meet consumer expectations and build long-term success in the competitive e-commerce market in Malaysia.